Effectiveness of Awareness Programme Regarding Warning Signs, Risk Factors, and Treatment of Stroke among Employees of Government Banks - Dutta, Monika; Ghai, Sandhya; Dhandapani, Manju; Kaur, Sandeep; Kaur, Parneet; Chaudhary, Umkita; Kaur, Karamjeet; Mall, Aradhana; Handa, Neha (International Journal of Nursing Research, 2023)
Aim: Stroke is progressively becoming a prime cause of early death and long lived ailment in adults globally due to lack of awareness of stroke. This leads to delay in seeking prompt treatment for stroke due to delay in reaching specialized health-care centers. The present study was done to determine the effectiveness of awareness program regarding warning signs, risk factors, and treatment of stroke among bank employees whose sedentary lifestyle makes them prone to get stroke. Materials and Methods: A quasi-experimental research study was carried out on bank employees. Total enumeration sampling technique was used and 100 bank employees were enrolled as study subjects. Questionnaire and teaching module that was validated by the experts in field of nursing and neurology was used for data collection. All the subjects were contacted personally for the data collection. They were asked to fill up the questionnaire and their biophysical measurements were done. The efficacy of the educational teaching module was assessed through pre- and post-educational intervention responses of the subjects using SPSS version. Results: The awareness regarding stroke improved after educational intervention. The awareness before the commencement of awareness program regarding stroke, its risk factors, warning signs, and treatment was 40.16%, 68.16%, 29.09%, and 44.60%, respectively, which improved to 94.80%, 86.83%, 81%, and 90, 20%. The overall awareness improved from 46.91% to 86.70%. Conclusion: Nurses and health-care professionals must take efforts to bring awareness through educational activities in general population keeping in mind the high risk groups for stroke.